BUMDesa Management Practices Driving Growth of Village Original Revenue: Praktik Pengelolaan BUMDesa yang Mendorong Pertumbuhan Pendapatan Asli Desa - Rizky Akbar; Hendra Sukmana (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Village-Owned Enterprises (BUMDesa) are strategic instruments for strengthening local economies and supporting village financial independence in Indonesia. Specific Background: BUMDesa Sumber Abadi Ngaban manages multiple business units contributing to the Village Original Revenue (PADes), yet faces managerial and legal challenges. Knowledge Gap: Limited studies examine how practical management principles within BUMDesa translate into measurable PADes growth at the village level. Aims: This study analyzes the management of BUMDesa Sumber Abadi Ngaban using Prajudi Atmosudirdjo’s management principles to understand its role in PADes growth. Results: Findings show that clear division of work, authority, discipline, direction, and team spirit supported the operation of four active business units, increasing PADes from IDR 120 million (2021) to IDR 240 million (2024), although planning and legal formalization remain constraints. Novelty: The study connects classical management principles with empirical BUMDesa practices and PADes data in a real village context. Implications: Strengthening planning capacity, human resources, and legal status is essential for optimizing BUMDesa governance and sustaining village revenue growth.